The experiences of public health nurses during the COVID‐19 in Taiwan: A qualitative study - Fei‐Ling Wu; Jui‐Chiung Sun; Hsueh‐Ching Wu; Mei‐Chen Su; Chia‐Ling Lin (Wiley, 2024)
Abstract Aim The coronavirus disease 2019 (COVID‐19) pandemic has had a substantial effect on frontline health care workers and caused public health nurses (PHNs) to come under various forms of pressure. PHNs face high‐risk challenges in their work environment, and their professional commitment and adaptability are key concerns. The aim of this qualitative study was to describe the experiences of PHNs during the COVID‐19 outbreak. Methods/Design Twenty PHNs who worked during the COVID‐19 outbreak were recruited from seven public health centres through posters. Data were collected through in‐depth interviews that comprised semi‐structured and open‐ended questions; subsequently, the data were analysed through content analysis. Results Three themes emerged from the study findings, namely (1) the disorderliness of COVID‐19 pandemic prevention work, (2) managing stress and fear, and (3) the establishment of a new normal. Because of the severity of the pandemic, the workload and stress associated with epidemic prevention policies continue to increase. PHNs may infect their family members and experience a sense of alienation and distance. They must also deal with irrationality and reactions in the people within their community. Conclusion Health department directors and policymakers should provide the necessary support and assistance to frontline pandemic prevention workers to increase the efficiency of pandemic prevention efforts. Patient or Public Contribution The participants agreed to participate in the qualitative study during the study period.